Content area teachers' challenges writing language objectives: A document analysis. Issue 1 (1st June 2020) - Balconi, Alexandra; Spitzman, Emily
Abstract : Teachers of English learners (ELs) often have solid knowledge in education theory and methodology but are challenged with identifying appropriate language demands in the content that they teach and creating language objectives (LOs) that focus on such demands. The document analysis study reported in this article examined the effectiveness of LOs from 60 lesson plans created by teachers enrolled in sheltered English immersion endorsement courses at a university in the northeastern United States to explore their ability to meet ELs' language needs. The data analysis demonstrated an overemphasis on productive skills, a limited scope of the language target or lack thereof, deficiencies related to language functions, and a tendency to view LOs as lesson activities. Following a discussion of these themes, the authors suggest practical recommendations for teacher educators and teachers to support ELs' language development and content learning.